2002
DOI: 10.1021/cm010694q
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Reactions of Iron Borates with Lithium: Electrochemical and in Situ Mössbauer and X-ray Absorption Studies

Abstract: Upon electrochemical reduction in a lithium cell, crystalline FeBO3 and Fe3BO6 give amorphous compounds, which can be cycled reversibly at low potential (Rowsell, J. Power Sources 2001, 97−98, 254). We report here capacities as high as 300 Ah/kg at the 14th cycle. The mechanism of reaction was investigated by step-potential electrochemical spectroscopy and in situ Mössbauer and X-ray absorption spectroscopies on electrochemical cells encapsulated in thin sealed plastic bags. These techniques confirm the reduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
2
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(45 citation statements)
references
References 22 publications
3
39
2
1
Order By: Relevance
“…This is because that Fe 3 BO 6 begins to decompose at around 950 1C and gives birth to Fe 2 O 3 and B 2 O 3 . This result is in agreement with that of IbarraPalos et al [12]. Meanwhile, a slow weight loss observed on TG curve is because of the volatilization of B 2 O 3.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…This is because that Fe 3 BO 6 begins to decompose at around 950 1C and gives birth to Fe 2 O 3 and B 2 O 3 . This result is in agreement with that of IbarraPalos et al [12]. Meanwhile, a slow weight loss observed on TG curve is because of the volatilization of B 2 O 3.…”
Section: Resultssupporting
confidence: 93%
“…The compound undergoes framework disintegration, yielding amorphous phase that can be cycled with high reversibility. In the report of Ibarra-Palos and co-workers [12], the Fe 3 BO 6 has capacity retention of about 225 mAh g -1 after 10 cycles. However, the electrochemical properties of Fe 3 BO 6 in previous work were all tested at rather low current densities (10 and 5 mA g -1 , respectively), which limits its potential applications.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the borates FeBO 3 and Fe 3 BO 6 , the structures do not allow intercalation and the Mössbauer results [12] confirmed that the first cycle destroyed the crystalline borates. However the materials were then able to continue to cycle reversibly between Fe 0 and Fe 2+/3+ states, with the latter phases being probably nanocrystalline or amorphous.…”
Section: Positive Electrode Materialsmentioning
confidence: 84%
“…Some transition metal borates exhibit catalytic activity 9 , magnetic behavior [10][11][12] and reversible Li-ion uptake [13][14][15] . In addition, a boron atom may adopt triangular oxygen coordination, where three oxygen atoms form B(sp2)-O bonds, or tetrahedral oxygen coordination, where four oxygen atoms form B(sp3)-O bonds.…”
Section: Introductionmentioning
confidence: 99%